2017
DOI: 10.1111/crj.12680
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pulmonary rehabilitation in COPD patients receiving long‐term oxygen therapy

Abstract: Those COPD patients receiving the LTOT benefited from the PR as much as those COPD patients not receiving LTOT. The former group had a higher increase in 6mWD and a higher reduction in dyspnea symptoms. Further studies are required to understand to what extent the severe chronic hypoxemic COPD patients could benefit from the PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Similar to the results of some studies in the literature and supporting the results of our previous studies, oxygen saturation increased after PR in patients with COPD in this study as well 34‐36 . In studies examining the relationship between the PR programme and smoking in terms of respiratory function test values, it is noteworthy that the results are contradictory 34‐39 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the results of some studies in the literature and supporting the results of our previous studies, oxygen saturation increased after PR in patients with COPD in this study as well 34‐36 . In studies examining the relationship between the PR programme and smoking in terms of respiratory function test values, it is noteworthy that the results are contradictory 34‐39 .…”
Section: Discussionsupporting
confidence: 90%
“…[34][35][36] In studies examining the relationship between the PR programme and smoking in terms of respiratory function test values, it is noteworthy that the results are contradictory. [34][35][36][37][38][39] In a single study in the literature comparing smoking and non-smoking COPD patients, it was observed that FEV 1 values did not change after PR. 14 However in our study FEV 1 values increased significantly in both groups.…”
mentioning
confidence: 99%
“…18,39 The originality of our study was to evaluate the benefits of a home-based PR in people with severe COPD receiving mostly long-term oxygen therapy and/or non-invasive ventilation. Only a few studies have been reported in this specific population, 10,40 but collectively these studies and our highlight that older people with chronic respiratory failure should be considered an appropriate candidate for PR.…”
Section: Dovepressmentioning
confidence: 71%
“…Smoking time and long-term oxygen therapy at home have been demonstrated to improve survival in patients with COPD [ 30 , 31 ]. Our program showed significant effects on smoking cessation and oxygen use in one-year management.…”
Section: Discussionmentioning
confidence: 99%